Novel insights into the kinetics, bio-based chemicals and mechanisms for tobacco industry waste pyrolysis - Xing Fan; Boyu Li; Yu Xi; Junping Bian; Wenhua Zi (Results in Engineering)
A comprehensive understanding of the pyrolysis mechanism of tobacco industry waste (TIW) is crucial for its efficient utilisation and environmental pollution reduction. In this study, the pyrolysis behaviour of TIW was systematically investigated using thermogravimetric analysis (TG), asymmetric peak deconvolution, and pyrolysis-gas chromatography/mass spectrometry (Py-GC/MS). The kinetics of the devolatilisation stage were determined using isoconversional methods, and the potential of TIW as a bio-based chemical feedstock was evaluated. The results revealed that the devolatilisation of TIW primarily occurred between 120 and 600 °C. The apparent activation energy (Eα) of tobacco stems (TS) and tobacco leaves (TL) increased with conversion degree(α), whereas the Eα of reconstituted tobacco sheets (RTS) first increased and then decreased as the α increased. The average apparent activation energy(E0) values were RTS (207.18 kJ•mol−1) ≈ TS (206.58 kJ•mol−1) > TL (172.28 kJ•mol−1). The devolatilisation stage of TIW was divided into four sub-stages: namely volatile substances breakdown, hemicellulose and pectin and nicotine breakdown, cellulose decomposition, and lignin breakdown. The E0 values for the four pyrolysis sub-stages were as follows: 126.59, 236.68, 198.09, and 241.90 kJ•mol−1 for TS; 114.67, 103.05, 97.90, and 120.08 kJ•mol−1 for TL; 155.26, 192.28, 176.07, and 283.91 kJ•mol−1 for RTS. The pyrolysis reaction followed a multi-step mechanism involving diffusion, geometrical contraction, and reaction order models. TIW was found to have high economic value, producing valuable chemicals such as furfural, nicotine, and 5-hydroxymethyl-2-furancarboxaldehyde. This study provides theoretical guidance for optimising TIW pyrolysis processes and supports the development of biorefinery technologies based on biomass resources.